DOE’S GRID MODERNIZATION INITIATIVE (GMI) AND CYBERSECURITY FOR ENERGY DELIVERY SYSTEMS (CEDS): SECURING CRITICAL INFRASTRUCTURE WITH CLOUD SOLUTIONS - Deneesh Narayanasamy (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of cloud technologies in grid modernization and cybersecurity represents a transformative approach to protecting critical energy infrastructure. This article examines how cloud engineering underpins the Department of Energy's Grid Modernization Initiative and Cybersecurity for Energy Delivery Systems programs, focusing on enhanced resilience and security measures. The article explores various aspects including Infrastructure as Code implementation, real-time monitoring capabilities, advanced threat detection systems, and interoperability standards. Through cloud-based solutions, utilities have achieved significant improvements in threat detection, incident response, and operational efficiency. The article also addresses emerging challenges and future considerations, emphasizing the role of quantum computing, edge computing, and blockchain technologies in shaping the future of grid security.